2012
DOI: 10.1007/s10142-012-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles for redox genes in ethanol sensitivity in Drosophila

Abstract: Whilst the effects and associated costs of excessive alcohol consumption in the human population are obvious at one level, the roles played by genetic factors at the molecular level are still unclear. Drosophila melanogaster has an alcohol response comparable to humans and is used as a genetic model to study the functional roles of genes regulated in response to ethanol. In the current study, the biological processes associated with behavioural responses to acute alcohol exposure in Drosophila have been analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Given the short exposure period of the flies to ethanol, the ROS effect is most likely due to its second messenger action [ 26 ] rather than due to a cell death mechanism. This is consistent with the recent report showing that expression of oxidative stress genes can be altered by ethanol exposure and their functions are essential for ethanol sensitivity [ 29 , 30 ]. It is possible that TSPO-deficiency induced ROS production could also participate in development of tolerance, but this effect must be mediated by cells other than neurons.…”
Section: Discussionsupporting
confidence: 93%
“…Given the short exposure period of the flies to ethanol, the ROS effect is most likely due to its second messenger action [ 26 ] rather than due to a cell death mechanism. This is consistent with the recent report showing that expression of oxidative stress genes can be altered by ethanol exposure and their functions are essential for ethanol sensitivity [ 29 , 30 ]. It is possible that TSPO-deficiency induced ROS production could also participate in development of tolerance, but this effect must be mediated by cells other than neurons.…”
Section: Discussionsupporting
confidence: 93%
“…A meta-analysis showed that only about 4% of the statistically most significant changes in expression (29 out of 737) were shared with two previous microarray studies (Morozova et al, 2006;Urizar, Yang, Edenberg, & Davis, 2007). Another group (Awofala, Davies, & Jones, 2012) also compared their analysis of mRNA abundance changes two hours after ethanol exposure to the microarray studies by Morozova et al (2006) and Urizar et al (2007). They report only a 9% overlap of their ethanol-response genes with the two other studies.…”
Section: Gene Discovery and Analysismentioning
confidence: 99%
“…Ethanol produces oxidative stress by causing an imbalance in redox reactions and increases the formation of reactive oxygen species (ROS) [47,48]. The increase in ROS levels activates detoxification mechanisms that act as antioxidants and reduce the synthesis of ROS [49]. Glutathione metabolism is among the detoxification mechanisms involved in the response to ethanol and was shown to be activated in D. meridionalis in our study.…”
Section: Discussionmentioning
confidence: 69%
“…In D. antonietae , we found evidence for the activation of the Wnt pathway, which plays a central role in several developmental processes, including neurogenesis [57]. This pathway may also be linked to neuronal apoptosis, which can be a result of exposure to ethanol present in volatile compounds produced by cacti [49]. In contrast, the Notch pathway was activated in D. meridionalis .…”
Section: Discussionmentioning
confidence: 99%